Water supply treatment sustainability of Panching water supply treatment process - water footprint approach - Edriyana, Abd Aziz; Marlinda, Abdul Malek; Syazwan, N. Moni; Nabil F., Zulkifli; Iqmal, H. Hadi (IOP Publishing Ltd, 2018)
In many parts of the world, freshwater is scarce and overexploited. The purpose of this study is to determine the water footprint of Water Supply Treatment Process (WSTP) at Panching Water Treatment Plant (WTP) as well as to identify the sustainability of the Sg. Kuantan as an intake resource due to the effect of land use development. The total water footprint (WF) will be calculated by using WF accounting manual. The results obtained shows that the water intake resource is still available but it is believed that it will not be able to cope with the increasing WF. The increment of water demand percentage by 1.8% from 2015 to 2016 has increased 11 times higher of the water footprint percentage, 19.9%. This result shows that the water consumption during the water supply treatment process is two times higher than the demand thus it shows the inefficient of the water management.